2013
DOI: 10.1111/jnc.12437
|View full text |Cite
|
Sign up to set email alerts
|

Alternative polyadenylation and miR‐34 family members regulate tau expression

Abstract: Tau pathologically aggregates in Alzheimer’s disease, and evidence suggests that reducing tau expression may be safe and beneficial for the prevention or treatment of this disease. We sought to examine the role of the 3’-untranslated region (3’-UTR) of human tau mRNA in regulating tau expression. Tau expresses two 3’-UTR isoforms, long and short, as a result of alternative polyadenylation. Using luciferase reporter constructs, we found that expression from these isoforms is differentially controlled in human n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 46 publications
0
96
0
1
Order By: Relevance
“…Thus, the loss or gain of function of these miRNA controls the generation of Aβ independently of the changes in APP expression. Similar studies have examined the miRNAs regulating tau expression (miR-34 family) [140] and the proteins involved in the hyperphosphorylation of tau observed in AD (for example, miR-26b indirectly affects cytoplasmic export of cyclin-dependent kinase 5 (Cdk5), a major tau kinase [141]) (Fig. 3a).…”
Section: Micrornas Studies In Admentioning
confidence: 91%
“…Thus, the loss or gain of function of these miRNA controls the generation of Aβ independently of the changes in APP expression. Similar studies have examined the miRNAs regulating tau expression (miR-34 family) [140] and the proteins involved in the hyperphosphorylation of tau observed in AD (for example, miR-26b indirectly affects cytoplasmic export of cyclin-dependent kinase 5 (Cdk5), a major tau kinase [141]) (Fig. 3a).…”
Section: Micrornas Studies In Admentioning
confidence: 91%
“…To date, researchers found several miRNA-binding sites and they were able to validate direct inhibition of human tau by miR-34a [56]. Another approach to inhibit NFT formation is represented by regulating the phosphorylation status of tau protein.…”
Section: Mirna-targeting Genes In Admentioning
confidence: 99%
“…It was suggested that this effect on tau was predominantly due to a reduction in ΔNp73 isoform expression and was mediated through an effect on JNK [55]. The p73/miR-34a axis has also been implicated in AD, as high levels of TAp73 and miR-34a have been found in brains from both mouse models of AD and AD patients [120][121][122]56].…”
Section: P73 and Alzheimer's Diseasementioning
confidence: 99%